Properties of foam concrete based on highly concentrated aluminosilicate binder suspension. Issue 1 (August 2020) - Sivalneva, M N; Strokova, V V; Kobzev, V A
Abstract: Cementless binders and building materials are promising. The article presents results of production of foam concrete compositions using high-concentration aluminosilicate binder suspension based on granodiorite. Their basic physical and mechanical characteristics and microstructural features are described. The method of multifactor experiment was used, which allows to vary the parameters: water-solid ratio, amount of binder component and stabilizing additive. Thus, during steps of mathematical planning, optimal parameters were recommended, the observance of which is necessary to obtain cementless cellular composites with the best properties.